Estudo da influência do meio de cultura na curva de morte de Aggregatibacter actinomycetencomitans induzida pela terapia antimicrobiana com luz azul - Salviatto, Luciana Toledo Costa (2021)
Periodontal disease (PD) is a highly prevalent chronic inflammatory disease around the world, affecting approximately 10% of the adult population, caused by bacterial biofilm. Antimicrobial therapy with blue light (aBLT) is based on the interaction of light with endogenous photosensitizers produced by microorganisms, such as metal-free porphyrins and flavins, in the generation of reactive oxygen species (ROS) and cell elimination. The goal of this work is to evaluate the potential of bacterial death by aBLT and the influence of BHI (brain heart infusion) culture media and blood agar on the death curve of the periodontopathic bacteria Aggregatibacter actninomycetencomitans. For this work, we u LED emitting at 403nm ± 15 with 1W of radiant power, the irradiance of 588,2 mW / cm2, and irradiation duration of 0, 1, 5, 10, 30 and 60 minutes in 2 different groups: A. actinomycetencomitans cultivated in BHI and A. actinomycetencomitans in blood agar. The plates were incubated in microaerophilia, in a bacteriological greenhouse, with a temperature regulated at 37◦ C during a period of 48h to count the colony-forming units (CFU / mL) and performed in triplicate. Spectroscopy and fluorescence microscopy were also carried out to investigate the presence of photosensitizers inside the microorganisms. Results: There was no statistical difference in the survival fraction of the colonies when A. actinomycetencomitans was cultivated in different culture media (p>0,05), however when the irradiation time reached 30 minutes (1.058 J/cm2), a biological and statistical reduction of microorganisms in both media was observed (p<0,05). The absorption spectrum and the analysis of fluorescence microscopy give indications of the presence of endogenous porphyrins inside these bacteria, regardless of the culture media.